Community-based Health Data Cooperatives Towards Improving the Immigrant Community Health: A Scoping Review to Inform Policy and Practice - Naeem, Iffat; AKM Nurul, Hossain; Vaska, Marcus; Goopy, Suzanne; Rashid, Ruksana; Kassan, Anusha; Aghajafari, Fariba; Ferrer, Ilyan; Kazi, Ahsan; Sadi, Iftekhar; O'Beirne, Maeve; Leduc, Charles; et al. (International Journal of Population Data Science, 2020)
Background In the case of immigrant health and wellness, data are the key limiting factor, where comprehensive national knowledge on immigrant health and health service utilisation is limited. New data and data silos are an inherent response to the increase in technology in the collection and storage of data. The Health Data Cooperative (HDC) model allows members to contribute, store, and manage their health-related information, and members are the rightful data owners and decision-makers to data sharing (e g. research communities, commercial entities, government bodies). Objective This review attempts to scope the literature on HDC and fulfill the following objectives: 1) identify and describe the type of literature that is available on the HDC model; 2) describe the key themes related to HDCs; and 3) describe the benefits and challenges related to the HDC model. Methods We conducted a scoping review using the five-stage framework outlined by Arskey and O’Malley to systematically map literature on HDCs using two search streams: 1) a database and grey literature search; and 2) an internet search. We included all English records that discussed health data cooperative and related key terms. We used a thematic analysis to collate information into comprehensive themes. Results Through a comprehensive screening process, we found 22 database and grey literature records, and 13 Internet search records. Three major themes that are important to stakeholders include data ownership, data security, and data flow and infrastructure. Conclusions The results of this study are an informative first step to the study of the HDC model, or an establishment of a HDC in immigrant communities.